Rapid ultrasound-assisted synthesis of controllable Zn/Co-based zeolitic imidazolate framework nanoparticles for heterogeneous catalysis - Yao, Bingqing (2022)
While metal-organic frameworks (MOFs) exhibit excellent potential in extensive catalytic reactions, predictably synthesizing MOF nanoparticles (NPs) with desired and uniform sizes remains a great challenge. Here, a mild and efficient ultrasound-assisted synthetic method has been developed to prepare ZIF-8, ZIF-67, and Co/ZIF-8 with well-designed particle size and morphology. By adjusting the cobalt content doped into a heterometallic ZIF-8 structure, tunable particle sizes ranging from 35 nm to over 300 nm have been achieved, resulting from the differences in nucleation and growth rates of zinc and cobalt ZIFs. Impressively, this as-obtained bimetallic Zn/Co-ZIF shows hierarchical porous structure with modified physicochemical properties, leading to a change of nitrogen adsorption-desorption characteristics. In addition, when used as a heterogenous catalyst, the bimetallic Co-doped ZIF-8 is demonstrated to have both enhanced catalytic performance for the activation of peroxymonosulfate (PMS) in organic dye degradation compared to pure ZIF-8, as well as superior structural stability, when compared to monometallic ZIF-67. This work provides a novel strategy for the predictable design and controlled fabrication of bimetallic MOF nanostructures with desired structures and compositions.